THEORETICAL FOUNDATIONS OF THE ADJECTIVE CATEGORY IN UZBEK LINGUISTICS - Ergasheva, Umida Kholikulovna (Journal of Higher Education and Academic Advancement, 2024)
In linguistics, significant work has been carried out on word categories, their classification. In the system of word categories, there is a specific place of quality, meaning-function, methodology. The adjective word category has been studied in depth in World linguistics, including Uzbek linguistics. Because the adjective is one of the main word categories in the Uzbek language. He characterizes the object, expressing the quality of the object. Adjectives describe all types of objects, expand, clarify, complement the perception of them. In a word, it creates the landscape of the real world, that is, they help to know and understand the world around us